Ekosistem Ekonomi Islam: Konsep, Prinsip, dan Strategi Penguatan di Indonesia: Islamic Economic Ecosystem: Concepts, Principles, and Strategies for Strengthening in Indonesia - Azwar, Azwar; Andi Wawan Mulyawan; Mukhtar Lutfi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to provide a comprehensive understanding of the Islamic economic ecosystem, encompassing its concepts, fundamental principles, pillars and actors, as well as instruments and strategies for its strengthening within the Indonesian context. The research employs a qualitative-descriptive approach based on an extensive literature review. The findings reveal that the main pillars of the Islamic economic ecosystem consist of the Islamic financial sector, the halal industry, ZISWAF, sharia-based micro, small, and medium enterprises (MSMEs), and the sharia-driven digital economy. These pillars are supported by key actors, including the government, regulators, academics, industry players, society, and Islamic institutions. Financial instruments (Islamic banks, sukuk, Islamic fintech), social instruments (zakat, infaq, sadaqah, waqf), and supporting infrastructure such as regulatory frameworks, halal certification, digital technology, and shariah-compliant human resources serve as crucial enablers of the ecosystem’s sustainability. The study also identifies Indonesia’s substantial potential to become a global hub for the Islamic economy, supported by its large Muslim population, expansive halal market, and national regulatory backing. Nevertheless, challenges remain, including low levels of shariah literacy, limited human resource capacity, suboptimal regulatory implementation, and intensifying global competition. Consequently, strategies for strengthening the ecosystem should focus on improving literacy and inclusion, fostering cross-sectoral collaboration, enhancing digital innovation, reinforcing adaptive regulation, and integrating education with the halal industry. Through these measures, Indonesia’s Islamic economic ecosystem has the potential to evolve into an inclusive, competitive, and sustainable system, contributing significantly not only to national development but also to the advancement of global civilization.